Molecular genetics of childhood, adolescent and young adult non‐Hodgkin lymphoma. (11th March 2016) - Miles, Rodney R.; Shah, Rikin K.; Frazer, J. Kimble
Summary: Molecular genetic abnormalities are ubiquitous in non‐Hodgkin lymphoma (NHL), but genetic changes are not yet used to define specific lymphoma subtypes. Certain recurrent molecular genetic abnormalities in NHL underlie molecular pathogenesis and/or are associated with prognosis or represent potential therapeutic targets. Most molecular genetic studies of B‐ and T‐NHL have been performed on adult patient samples, and the relevance of many of these findings for childhood, adolescent and young adult NHL remains to be demonstrated. In this review, we focus on NHL subtypes that are most common in young patients and emphasize features actually studied in younger NHL patients. This approach highlights what is known about NHL genetics in young patients but also points to gaps that remain, which will require cooperative efforts to collect and share biological specimens for genomic and genetic analyses in order to help predict outcomes and guide therapy in the future.